EDUKASI KESEHATAN JIWA PADA SISWA SMA DI MASA PANDEMI COVID-19 - Wike Astaria; Adek Putri; Mutmainah Mutmainah; Auliah Triski Syahputri; Yosi Oktarina (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2022)
ABSTRACT During the pandemic, all people, young and old, feel the impact, including school children. The problems faced by school children include changes in methods in learning which are usually carried out directly through face-to-face, into learning in a network (online). This can cause boredom in students because they have to continuously stare at their gadget screens which can have an impact on students' mental health. This service activity is partnered with SMAS Pelita Raya Jambi City. This service activity aims to provide education on how to maintain mental health in students during the pandemic. The number of participants who took part in this activity was 32 students. Activities are carried out in the school hall. Based on the results of the evaluation, participants felt enthusiastic about participating in the activity and after being given counseling there was an increase in students' knowledge about mental health and how to maintain mental health in school children. It is hoped that after providing mental health education to school children, students can recognize, maintain, and improve mental health so that students can be more productive in carrying out daily activities Key Words : Health Mental, School. Student ABSTRAK Pada masa pandemi semua kalangan baik tua maupun muda merasakan dampaknya termasuk di dalamnya anak sekolah. Permasalahan yang dihadapi oleh anak sekolah diantaranya perubahan metode dalam pembalajaran yang biasanya dilakukan secara langsung melalui tatap muka, menjadi pembelajaran dalam jaringan (daring). Hal ini dapat menimbulkan kejenuhan pada siswa karena harus terus menerus menatap layar gadget-nya yang dapat berdampak pada kesehatan jiwa siswa. Kegiatan pengabdian ini bermitra dengan SMAS Pelita Raya Kota Jambi. Kegiatan pengabdian ini bertujuan untuk memberikan edukasi mengenai cara menjaga kesehatan mental pada siswa di masa pandemi. Jumlah peserta yang mengikuti kegiatan ini sebanyak 32 orang siswa. Kegiatan dilakukan di aula sekolah. Berdasarkan hasil evaluasi, peserta merasa antusias mengikuti kegiatan dan setelah diberikan penyuluhan terdapat peningkatan pengetahuan siswa mengenai kesehatan jiwa dan cara menjaga kesehatan jiwa pada anak sekolah. Diharapkan setelah pemberian edukasi kesehatan jiwa pada anak sekolah, siswa dapat mengenal, menjaga, serta meningkatkan kesehatan jiwa sehingga siswa dapat lebih produkti dalam menjalani aktivitas sehari-hari. Kata Kunci : Kesehatan Jiwa, , Sekolah, Siswa